1997
DOI: 10.1021/ic970010+
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Inversion around a Seven-Coordinated Cobalt Center Induced by an Interaction between Sugars and Sulfate Anions

Abstract: Novel seven-coordinated cage-type cobalt(II) complexes containing N-glycosides from mannose-type aldoses and tris(2-aminoethyl)amine (tren), [Co((aldose)3tren)]X2·nH2O (1a·5H2O, aldose = d-mannose (d-Man), X = Cl-; 1b·5H2O, aldose = 6-deoxy-l-mannose (l-Rha), X = Cl-; 2a·4H2O, aldose = d-Man, X = Br-; 2b·H2O, aldose = l-Rha, X = Br-) and [Co((aldose)3tren)]SO4·nH2O (3a·4H2O, aldose = d-Man; 3b·3H2O, aldose = l-Rha), where (aldose)3tren is tris(2-(aldosylamino)ethyl)amine, were prepared and characterized by ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“… (a) Helicity inversion of a Co(II) complex induced by nitrate anion; [82] (Chemdraw colour was changed from the original figure). (b) Switching of helical sense of an AIB foldamer upon formation of different boronate ester; [83] (Chemdraw colour was changed from the original figure) (c) Sulfate induced reversible helicity switching of a labile Co(II) complex; [85] Adapted with permission from Ref. [85], Copyright 1997, American Chemical Society.…”
Section: Chiroptical Switching Of Helicitymentioning
confidence: 99%
“… (a) Helicity inversion of a Co(II) complex induced by nitrate anion; [82] (Chemdraw colour was changed from the original figure). (b) Switching of helical sense of an AIB foldamer upon formation of different boronate ester; [83] (Chemdraw colour was changed from the original figure) (c) Sulfate induced reversible helicity switching of a labile Co(II) complex; [85] Adapted with permission from Ref. [85], Copyright 1997, American Chemical Society.…”
Section: Chiroptical Switching Of Helicitymentioning
confidence: 99%
“…Yano et al reported chiral inversion [47] induced around a seven-coordinated cobalt center by interaction between sugars and sulfate anions. New cage-type cobalt(II) complexes that consist of N-glycosides from mannose-type aldoses and tris(2-aminoethyl)amine (tren), [Co((aldose) 3 tren)]X 2 ·nH 2 O (where X = Cl − , Br − ) and [Co((aldose) 3 tren)]SO 4 ·nH 2 O exhibited C 3 helical configuration inversion around the Co(II) center.…”
Section: Anion Controlled Switching Of Amide Complexesmentioning
confidence: 99%
“…The sulfate anion situates itself into the complex cation cavity along the C3 axis. Rha = 6-deoxy-l-mannose[47]. Copyright 1997 American Chemical Society.…”
mentioning
confidence: 99%
“…To the best of our knowledge complex [Ni(Hsal HMan)(tptz)]ClO 4 is the first transition metal complex exhibiting a non-chair conformation of a mannopyranose ring. In transition metal complexes derived from mannose or the related L L-rhamnose, containing more flexible co-ligand moieties like (aminoalkyl)amines [48][49][50][51][52][53] instead of the rigid tptz molecule or obtained from less donor-functionalized sugar moieties, 54-57 the pyranose ring generally adopts the expected chair conformation.…”
Section: Pyranose Ring Conformationmentioning
confidence: 99%